Conception of a mobile health application targeting early postoperative physiotherapeutic care after total knee replacement, a qualitative study - Hakam, Hassan Tarek; Ramadanov, Nikolai; Garzuzi, Awda; Salzmann, Mikhail; Hofmann, Hannes; Muehlensiepen, Felix; Becker, Roland; Prill, Robert (Frontiers in Surgery, 2025)
IntroductionMobile applications targeting physiotherapeutic care after total joint replacements are increasing in popularity among end-users. However, these applications were primarily conceived out of financial interest and lack an evidence-based programs tailored to the specific needs of the target population. The primary objective of this study is to describe the conception of an evidence-based mobile health application that targets early postoperative physiotherapeutic care after total knee replacement (TKR).MethodsA literature search of eHealth applications targeting physical therapy after TKR was carried out. Articles were then screened and suggestions as well as recommendations were extracted to inform the design of a new application. The beta version of the application was then passed onto experts for evaluation. Final changes were then undertaken to account for the expert's opinions.ResultsSeveral reviews with recommendations for the design of applications targeting patients after total joint replacement were identified. Primarily, mobile applications targeting rehabilitative care after TKR need to be tailored to the needs of the elderly population. Additionally, no unified rehabilitative physiotherapeutic (PT) program was found reflecting a discrepancy regarding what exercises are most useful. A comparison of different programs yielded no significant difference favoring one single exercise regimen.DiscussionAs the elderly population was shown to be less proficient regarding the use of new technologies, the application at hand was explicitly made simple. Elements of different PT programs were incorporated and quadriceps strengthening exercises were included. application was composed based on the findings of the reviewed literature and then subsequently modified to incorporate the expert's suggestions. Experts mainly expressed concerns regarding the safety of patients during unsupervised physical therapy as well as the safety of the recorded data. Thus, password protection and a split between the physician's and the patient's interface was created.